Penggunaan Materai yang Di Scan pada Surat Kuasa di Bawah Tangan dalam suatu Perjanjian - Fika Pratiwi; I Ketut Sukadana; I Putu Gede Seputra (Warmadewa Press, 2020)
The use of stamp duty is very important for the completeness of a document where the stamp implicitly shows that the document owner has paid stamp duty tax to the state. However, now a document can be sent via various media such as email by scanning a document. Based on this background, this research was conducted with the aim of describing the regulation of a power of attorney under hand and an agreement letter according to the Civil Code and how the validity of the power of attorney under hand with a scanned stamp which then sent via email is. The research method used is normative legal research. The results of this study indicated that the arrangement of power of attorney under hand and an agreement letter according to the Civil Code has been regulated in Article 1792 to Article 1819 of the Civil Code. The power of attorney, of course, is also based on the agreement of the two parties as it has met the requirements according to the Civil Code in Article 1320 concerning the Terms of Legality of the Agreement. In addition, the power of attorney under hand using a scanned stamp sent via email can be said to be legal according to law because there is a stamp duty in a document as stated in Article 1 Paragraph 6-7 of Government Regulation Number 82 of 2012 concerning Information and Electronic Transactions.